FARMER’S PERCEPTION TOWARDS UTILIZATION OF CATTLE AS TOURIST ATTRACTION IN TABANAN REGION, BALI - N. W. T, Inggriati; Suarta, I G.; Warmadewi, D. A. (Majalah Ilmiah Peternakan; Vol 22 No 2 (2019): Vol. 22 No.2 (2019), 2019)
The study aims at determining the level of behavior and cattle farmers expectation for using cattle as agro tourist attraction, analyze the cattle breeders income and the relationship between breeders behavior and expectation including their perception of agro-tourism activities using cattle as attraction. It was conducted at Penebel and Marga districts, Tabanan regency. The respondents were collected as quota; 50 breeders were interviewed in 6 agro-tourism places such as Somya Pertiwi and Jatiluwih, Taman Sari Buana, Rumah Desa, tourist village of Pinge, and Cau Coklat. The data was analyzed in descriptive qualitative and correlation analysis. It showed that 1) farmers behavior towards the existence of agro-tourism using cattle as tourist attraction considered to be good; 2) income of farmers participation using cattle as tourist attraction range between Rp. 50.000 - and Rp. 300.000,- in ploughing activity, and 3) positive relationship between farmers behavior and expectation and their perception towards the development of agro-tourism business who use cattle as attraction. It can be concluded that 1) breeders have good behavior towards the development of agro-tourism business; 2) breeders gained extra income by participating in agro-tourism activities in order to achieve income by selling their cattle; 3) breeders have better behavior and higher expectation which is the better perception towards the use of cattle in agro-tourism business activities. Finally, suggestions such as 1) investors in agro-tourism business should co-operate with famers in their surroundings to run the activities; 2) Breeders should encourage raising cows instead of bulls since they are tame and increase population of cattle in their area; 3) local government should play important role in development of agro-tourism business i.e. village roads construction so it can encourage the visitors to come to the location. All of those will positively affect the prosperity of local breeders